Effects of Low-Dose Testosterone Undecanoate Treatment on Bone Mineral Density and Bone Turnover Markers in Elderly Male Osteoporosis with Low Serum Testosterone. (4th March 2013) - Wang, Yan-Jiao; Zhan, Jun-Kun; Huang, Wu; Wang, Yi; Liu, Yuan; Wang, Sha; Tan, Pan; Tang, Zhi-Yong; Liu, You-Shuo
Abstract : This prospective 2-year, single-center, randomized, placebo-controlled, open-label clinical trial was performed to evaluate the efficacy of low-dose testosterone undecanoate (TU) treatment on bone mineral density (BMD) and biochemical markers of bone turnover in elderly male osteoporosis with low serum testosterone. A total of 186 elderly male osteoporosis patients with low serum testosterone were randomized into three groups: low-dose TU (20 mg, per day), standard-dose TU (40 mg, per day), and placebo group with a 24-month followup. Since the 6th month in standard-dose TU group or since the 12th month followup in low-dose TU group and throughout the study, lumbar spine and femoral neck BMD and serum levels of free testosterone, estradiol, and bone alkaline phosphatase significantly increased. There were no significant differences between groups of low-dose TU and standard dose TU in the percentage of changes of these data since the 18th month followup and throughout the study. No side effects on prostate glands including prostate specific antigen were found. In conclusion, low-dose TU (20 mg, per day) may be a cost effective and safe protocol for treating elderly male osteoporosis with low serum testosterone.